Regional Economic Development Strategy: Increasing Local Generated Domestic Revenue of the Regional-Owned Enterprises in the Oil and Gas Sector - Qurbani, Indah Dwi; Sumarno, Theresia; Cassy, Retno W. N (Brawijaya Law Journal, 2020)
This paper illustrates how to develop a local development strategy in the establishment regulation of regional enterprises in the oil and gas sector in Bojonegoro District, Indonesia. This paper focuses on the locally generated domestic revenue in Bojonegoro, which have believed to be one of the most important strategies in their economic development. The oil and gas sector has contributed to almost 50% of the regional economic growth in Bojonegoro. However, the community in the region has not yet received an optimal benefit from the contribution as this sector only contributes 4.6% for its local employment in 2018 in comparison with the agrarian sector which contributes 36% for its local employees. The legal research conducted in this paper is juridical normative research by emphasising the establishment arrangement of the oil and gas regional enterprises to increase the locally generated domestic revenue from the sector. According to the Ministry Regulation of Ministry of Energy and Mineral Resources (MoEMR) Republica of Indonesia No. 1, 2008 on Guidelines for the Exploitation of Petroleum Mining in Mature Field stated that any Local (Village) Enterprise Unit ("KUD") or Regional Local Enterprises ("BUMD").